2017
DOI: 10.5194/acp-2017-899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A long-term time series of global and diffuse photosynthetically active radiation in the Mediterranean: interannual variability and cloud effects

Abstract: Abstract. Measurements of global and diffuse photosynthetically active radiation (PARproperties also contribute to produce small radiative effects on PAR in summer. 34The cloud radiative effect has been de-seasonalized to remove the influence of annual irradiance variations.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…This behavior relates the higher cloud cover and higher frequency of overcast skies with the higher values of kPAR, while, in summer the lower frequency of clouds favors a high penetration of solar radiation to the surface, and therefore the decrease in kPAR. Similar results were reported by Trisolino et al (2018) who estimated a mean value of 0.39 ± 0.08 with a marked seasonal trend with maxima around 0.50 in winter and minima at about 0.25-0.30 in summer. On the other hand, kPAR maximum values for clear-sky were also found in winter months, due to the lower solar elevation angles in this season which involve a higher atmospheric path for the solar radiation favoring the attenuation of PARGlobal and the increase of PARDiffuse.…”
Section: Effect Of Sky Conditions On Par-to-total Ratio and Par Diffu...supporting
confidence: 90%
See 2 more Smart Citations
“…This behavior relates the higher cloud cover and higher frequency of overcast skies with the higher values of kPAR, while, in summer the lower frequency of clouds favors a high penetration of solar radiation to the surface, and therefore the decrease in kPAR. Similar results were reported by Trisolino et al (2018) who estimated a mean value of 0.39 ± 0.08 with a marked seasonal trend with maxima around 0.50 in winter and minima at about 0.25-0.30 in summer. On the other hand, kPAR maximum values for clear-sky were also found in winter months, due to the lower solar elevation angles in this season which involve a higher atmospheric path for the solar radiation favoring the attenuation of PARGlobal and the increase of PARDiffuse.…”
Section: Effect Of Sky Conditions On Par-to-total Ratio and Par Diffu...supporting
confidence: 90%
“…autumn but mainly in spring when the maximum absolute values of CREGlobal are observed. This seasonal pattern with maximum values (in absolute terms) in April for both CREGlobal and CREDiffuse was also found byTrisolino et al (2018) forPAR and Pyrina et al (2015) in the shortwave range in the Mediterranean basin, who associated this pattern to elevated values of cloud optical thickness in this month.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…No ASVs were found enriched in spring AW and MS, indicating freshly generated and hence, recently populated MS, or a strong effect of environmental parameters on both AW and MS communities. The slight increase in seawater temperature and photosynthetically active radiation ( Trisolino et al, 2018 ) triggered an increase in primary production as indicated by the increasing chlorophyll a concentrations ( Supplementary Figure S5 ) favoring copiotrophic opportunistic prokaryotes such as Rhodobacterales (ASV4), Flavobacteriales (ASV5, 11 and 140) and Opitutales (ASV9; Wagner-Döbler and Biebl, 2006 ; Chafee et al, 2018 ; Jain et al, 2020 ). In summer, 50 ASVs were enriched in the AW as compared to MS and 68 ASVs in the MS over AW.…”
Section: Resultsmentioning
confidence: 99%